Hubungan Transisi Demokrasi Dengan Industri Minyak di Nigeria - , WINANDRIYO KUN ANGGIANTO; , Drs. Samsu Rizal Panggabean, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Democratization have been processed in Nigeria for more than 30 Years. Democratization also has strong relations to politics integrity and civil development. In Nigeriaâs case, where the oil industry is the main factor of social life, making the oil industry as the solid background of democracyâs transition on 1999. This thesis is seeing that stateâs depedency on oil industry has an influence for the process of democratization and any other implication following the transition.